An electrode-supported fabrication of thin polybenzimidazole membrane-based polymer electrolyte membrane fuel cell. (20th April 2018) - Yuk, Seongmin; Lee, Dong-Hyun; Choi, Sungyu; Doo, Gisu; Lee, Dong Wook; Kim, Hee-Tak
Abstract: H3 PO4 -doped polybenzimidazole (PBI) membranes have been employed for high temperature polymer electrolyte membrane fuel cell (HT-PEMFC). Although a thinner PBI membrane is beneficial in enhancing power performance, the use of thin PBI membrane has been hindered by its poor mechanical property and consequent difficulty in membrane handling during membrane electrode assembly (MEA) fabrication. Here, novel fabrication route to realize a thin PBI membrane (∼35 μm)-based HT-MEA is presented. The key feature of the process is to fabricate thin blend membrane of PBI and poly(ethylene glycol) (PEG) and laminate the blend membrane to anode gas diffusion electrode (GDE) followed by H3 PO4 doping. The introduction of PEG to PBI film enables the tight bonding of the membrane to the GDE at a mild lamination temperature and mitigates the membrane expansion with the doping, preserving the tight interfacial bonding. Due to the lowered membrane thickness, the corresponding MEA exhibits a high power density of 264 mW cm -2  at 0.6 V. Therefore, the new fabrication strategy based on the blend of PBI/PEG is highly effective in improving both process and power performance of HT-MEA. Graphical abstract: